Brassica Oilseeds Breeding and Management (Journal of Oilseed Brassica, 2026)
The book “Brassica Oilseeds Breeding and Management” presents an unprecedentedly thorough collection of information on the basic and strategic research of breeding and management of Brassica oilseeds crops. This book is a result of an imperative need and demand from the researchers, teachers, students, and interest by the publishers (CABI) to bring out the comprehensive information on Brassica oilseeds crops. It covers and integrates worldwide literature in the field of oilseed Brassica research upto 2015, setting it apart from other books that are only of regional importance. By compiling information of decades from formerly scattered research into a single globally-minded volume, Brassica Oilseeds Breeding and management provides these deeply desired updates and improvements. It is inspirational that Prof. Arvind Kumar, Vice Chancellor, Rani Lakshmi Bai Central Agricultural University, Jhansi, India, Prof. Surinder S. Banga, ICAR-National Professor, Punjab Agricultural University, Ludhiana, India, Dr. Prabhu Dayal Meena, Principal Scientist, ICAR-Directorate of Rapeseed-Mustard Research, Bharatpur, India and Dr. Priya Ranjan Kumar, Founder Director, National Research Centre on Rapeseed-Mustard, Bharatpur, India has bring out this useful book Brassica Oilseeds Breeding and Management. The book, foreword written by Prof. Ting-Dong Fu, Huazhong Agricultural University, Institute of Crop Genetics & Breeding, Wuhan, China. The book is published by internationally repute publisher CABI and priced at 144, could be considered and recommended for the institutes/ university libraries, personal collection for teaching and research oilseeds Brassica.